Kajian Sosiolinguistik Penggunaan Bahasa dalam Percakapan Mahasiswa Semester V Prodi Pendidikan Bahasa dan Sastra Indonesia STKIP PGRI Trenggalek - Suprapti Suprapti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The use of language in speech in everyday life has a big influence on the articulation of communication and interaction between humans. This interaction creates a unity that binds various differences. Therefore, linguistic diversity is unique in the field of communication. The important role of communication tools is to support clarity and the functioning of social life. The use of language in educational institutions is greatly influenced by the environment. As a result, the dialects used by Indonesian students are very unique and diverse. In general, this research aims to determine the diversity of languages ​​used by various students in educational institutions and their environments, especially Indonesian Language and Literature students.